Children of a lesser god: exclusion of chronic kidney disease patients from clinical trials. Issue 7 (27th February 2019) - Zoccali, Carmine; Blankestijn, Peter J; Bruchfeld, Annette; Capasso, Giovambattista; Fliser, Danilo; Fouque, Denis; Goumenos, Dimitrios; Ketteler, Markus; Massy, Ziad; Rychlık, Ivan; Jose Soler, Maria; Stevens, Kate; et al.
Abstract: The exclusion of chronic kidney disease (CKD) patients from clinical trials—particularly cardiovascular trials—remains a long-standing, unsolved problem, which prevents the optimization of clinical care in these patients. The situation recalls the insufficient recruitment of women in cardiovascular trials until the 1980s, a problem that was only resolved following regulatory interventions. Regulatory agencies are in a unique position to promote recruitment of CKD patients in clinical trials. The main stakeholders, namely patients' associations and scientific societies, should make major lobbying efforts to persuade these agencies that the issue is an absolute public health priority.